Pengendalian Persediaan Bahan Baku Oli Untuk Mesin Diesel Tipe G4J-801, G5J-801 dan G7J-801 di PT. Hansan Asembling – Malang - Rony Prabowo (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2017)
Inventories of raw materials is one of the most important elements in the company's operations are continuously must be obtained, processed and resold. The raw material is meant for the smooth running of production operations set. So, we need an optimum inventory levels to meet the needs of both the quantity, quality and time at a low cost. For that we need a system of planning and inventory control are best - well, that inventories of raw materials should be defined and calculated correctly and accurately in order to obtain a low total cost of inventory that can minimize the cost of production. Forecasting approach is expected to represent the number of actual demand in the coming period. Based on the number of requests of forecasting results can be determined raw material inventory control. By using EOQ then firms will be able to minimize the cost of raw material supplies of oil. Companies should pay attention to the order of recording historical data of oil, classification of costs - the cost of orders and storage costs, because such data is necessary to obtain optimal results inventory control.